2017
DOI: 10.1001/jamainternmed.2017.2309
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Fecal Immunochemical Test in Patients at Increased Risk for Colorectal Cancer

Abstract: The potential role of the fecal immunochemical test (FIT) for screening patients at increased risk for colorectal cancer (CRC) has not yet been elucidated.OBJECTIVE To assess the diagnostic accuracy of FIT for CRC or advanced neoplasia (AN) in asymptomatic patients at above-average risk.DATA SOURCES MEDLINE, EMBASE, Cochrane Library, and gray literature sources through August 2016.STUDY SELECTION Diagnostic studies evaluating the accuracy of FIT for CRC or AN in patients with a personal or familial history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 47 publications
3
57
0
1
Order By: Relevance
“…Our findings are consistent with two prior systematic reviews that informed our study methods (17,18), one of which quantified performance characteristics for CRC only and included studies with the less accurate and potentially biased surrogate reference standard of two-year follow-up without a CRC diagnosis (17). The other systematic review quantified performance characteristics for both CRC and advanced adenoma, but only included studies of high-risk persons (18). In addition, our searches identified a recent systematic review by Gies and colleagues that assessed seven FIT brands across 22 studies (60).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings are consistent with two prior systematic reviews that informed our study methods (17,18), one of which quantified performance characteristics for CRC only and included studies with the less accurate and potentially biased surrogate reference standard of two-year follow-up without a CRC diagnosis (17). The other systematic review quantified performance characteristics for both CRC and advanced adenoma, but only included studies of high-risk persons (18). In addition, our searches identified a recent systematic review by Gies and colleagues that assessed seven FIT brands across 22 studies (60).…”
Section: Discussionsupporting
confidence: 91%
“…Rather than develop and register a new formal protocol, we used two prior systematic reviews as guides for our study methodology (17,18). We followed standard procedures for systematic reviews and reported results according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines (19,20).PLEASE USE THE 2009 ANNALS PRISMA STATEMENT article for this reference.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports indicated that likelihood ratios above 10 provide strong evidence to make a definitive diagnosis in most circumstances. 31,32 Thus, we considered that an H 2 FPEF score of 7 points was a clinically meaningful cutoff point from the viewpoint of specificity and LR+ in the present study. This suggests that more careful observation and intensive risk reduction treatment could be needed to treat outpatients with a high H 2 FPEF score (≥7 points).…”
Section: Discussionmentioning
confidence: 99%